KUALITAS INFORMASI DATA STATUS GIZI BALITA DENGAN MEMANFAATKAN SOFTWARE WHO ANTHRO - Al Rahmad, Agus Hendra (PERSATUAN AHLI GIZI INDONESIA, 2020)
Nutritionists must be able to use technology and information to produce information on the quality and quantity of nutritional status for a toddler. The research objective was to assess WHO Anthro software in providing better data and information quality of child nutritional status. A quasi-experimental research design was selected in the intervention by using electronic software and manuals in two districts involving 40 nutritionists in community health centers. Primary and secondary data was collected through interviews and observations using questionnaires. Training in the experiment group by using the tool WHO Anthro Software v3.2.2 and the control group used a manual book provided by the Ministry of Health of Indonesia. Dependent t-test and independent t-test, using the R, was used to analyze the differences in the information quality before and after the intervention and between the two groups. The results showed a significant improvement in the quality of nutrition information status in both groups (p-value 0,05). Improvement was better in the intervention group using WHO electronic software (p-value 0,05) than that in the group using the manual intervention. Also, the recording and reporting outputs model based on electronics provide more information, and useful in nutrition program planning, monitoring, and evaluation. The use of electronic-based systems is better quality and more data analysis outputs, both for monitoring planning and nutrition program evaluation as well as decision-making support.ABSTRAKPengembangan sumber daya tenaga gizi di puskesmas melalui penguasaan teknologi dan informasimenjadi sangat penting, untuk menghasilkan informasi data status gizi balita yang berkualitas danberkuantitas. Tujuan penelitian adalah untuk melakukan penilaian pengunaan software WHO Anthro dalammeningkatkan kualitas data dan informasi status gizi balita. Penelitian berdesain Quasi Experiment perludilakukan dengan intervensi elektronik dan manual pada dua kabupaten/kota, melibatkan 40 ahli gizi diPuskesmas. Data primer dan sekunder dilakukan secara wawancara dan observasi menggunakankuesioner. Pelatihan menggunakan alat Software WHO Anthro v3.2.2 dan buku Kepmenkes RINo:1995/MENKES/SK/XII/2010. Analisis kualitas informasi yaitu Dependent T-Test dan Independent T-Test,menggunakan program R. Hasil intervensi masing-masing kelompok menunjukkan peningkatan terhadapkualitas informasi status gizi (p 0,05). Kelompok intervensi menggunakan WHO Anthro menunjukkanpeningkatan lebih baik (p 0,05) dibandingkan intervensi manual. Selain itu, pencatatan dan modelpelaporan berbasis elektronik dapat mengeluarkan output informasi yang lebih banyak, dan bermanfaatdalam perencanaan program gizi, monitoring dan evaluasi. Penggunaan sistem berbasis elektronik secarakualitas lebih baik, dan output analisis datanya lebih banyak, baik untuk perencanaan monitoring danevaluasi program gizi maupun sebagai pendukung pengambilan keputusan.